Navier-Stokes solutions for steady parallel-sided pendent rivulets - Tanasijczuk, Andres Jorge (2010)
We investigate exact solutions of the NavierStokes equations for steady rectilinear pendent rivulets running under inclined surfaces. First we show how to find exact solutions for sessile or hanging rivulets for any profile of the substrate (transversally to the direction of flow) and with no restrictions on the contact angles. The free surface is a cylindrical meniscus whose shape is determined by the static equilibrium between gravity and surface tension, by the shape of the solid surface, and by the contact angles on both contact lines. Given this, the velocity field can be obtained by integrating numerically a Poisson equation. We then perform a systematic study of rivulets hanging below an inclined plane, computing some of their global properties, and discussing their stability.